Konseling Kedukaan: Dampak Stres terhadap Kesehatan Emosional dan Fisik dalam Proses Kedukaan - Amalia, Aura Nilam; Miftah, Muhammad; Rahma, Alvina; Ilmi, Muhammad Ilham Aliyuddin Nur (JURNAL KONSELING GUSJIGANG, 2025)
This study investigates the effectiveness of Cognitive Behavioral Therapy (CBT) in reducing emotional and physical symptoms associated with the grieving process. Grieving can cause complex emotions, depression, and physical issues like sleep disorders and social disengagement. This review emphasizes the significance of cognitive behavioral therapy (CBT) in assisting individuals in changing negative thought patterns, regulating emotions, and adopting healthy habits when mourning. CBT approaches including reframing and relaxation have been demonstrated to lessen melancholy, anger, and stress while also improving emotional regulation. The findings indicated that structured CBT therapies can help with bereavement management, enhance emotional and physical health, and provide direction to counselors. This study concludes that cognitive behavioral therapy (CBT) is an effective strategy for assisting those experiencing sorrow, facilitating a healthier adjustment to loss, and improving overall well-being.